Gdyby nie Malik… - Żurakowska, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents the profile of the scholar, based on his cooperation with the regional radio that resulted in a series of radio programs on literature. In the archive of Radio Lublin there are twelve broadcasts on the subject matter that fascinated Malik – literary biographies, Prus and contemporary writers. Currently these tapes are not available to the public, which renders the presentation of some of them all the more interesting. The article includes a description and an analysis of selected programs, cites parts of the recordings and presents the circumstances of the registration of the material. The programs let the audience get acquainted with the scholar’s specific argumentation style, his knowledge of authors’ biographies, the passion with which he studied literature and his unusual attachment to Lublin and the region. The listener also learns about the people who were important to the professor, his idols; Malik often referred to the figure of the great literary scholar Prof. Stanisław Fit, whom he called the Master. Attached to the article is the list of the programs that are held in the Radio Lublin archive and that Prof. J. Malik took part in.